Increasing Indonesian Language Learning Results Models of Cooperative Learning Talking Stick Type - Uswa Khasanah (Universitas Sebelas Maret, 2020)
The purpose of this study was to improve the learning outcomes of students in the Indonesian language muple in grade II elementary schools with a cooperative talking stick learning model. The research carried out was to use two cycles of Classroom Action Research (CAR), with each cycle consisting of one meeting. The stages of each cycle are planning, implementing, observing and reflecting. Each meeting was conducted a knowledge test using formative tests and summative tests to determine the development of students. In the first cycle, the students who completed after carrying out the summative test were 62%. In cycle II, students completed after carrying out summative tests of 86%. These results indicate that the cooperative talking stick type learning model can improve student learning outcomes, especially the Class II Indonesian language muple at SD N TIMBULSOKO 1.